Electrospun composite nanofibers and their multifaceted applications - Sahay, Rahul (2013)
The re-exploration of the nanostructure production technique known as electrospinning was carried out in the past decade due to its simplicity and uniqueness of producing nanostructures. As nanotechnology is one of the most promising and growing technologies today, a large amount of work is being carried out in an extensive area and shows an extremely huge potential for miraculous works in the fields of medicine and biotechnology. These nanostructures were found to be of great significance because of their inherent properties such as large surface area to volume ratio and the engineered properties such as porosity, stability and permeability. The functionality and applicability of these nanostructures were further improved by incorporating secondary phases either during electrospinning or in the post-processing resulting in the composite nanostructures. These secondary phases may include metal oxides, carbon nanotubes, precious metals, gold nanoparticles and hydroxyapatite. Nanofibrous materials that mimic the native extracellular matrix (ECM) and promote the adhesion of various cells are being developed as tissue-engineered scaffolds for the skin, bone, vasculature, heart, cornea, nervous system and other tissues. The article discusses in detail the applicability of these composite fibers in energy, sensors, filters, biotechnology and details the technological issues, research challenges and future trends.